2016
DOI: 10.1038/srep30591
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Salmonella as intracellular factory for effective killing of tumour cells

Abstract: Salmonella have many desirable properties as antitumour-agent due to its ability to proliferate inside tumours and induce tumour regression. Additionally, this bacterium can be genetically engineered to deliver therapeutic proteins intratumourally. The main limitation of this approach is the efficient release of therapeutic molecules from intratumoural bacteria. Here we have developed an inducible autolysis system based in the lysis operon of the lambda phage that, in response to anhydrotetracycline, lysates S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 59 publications
1
50
0
1
Order By: Relevance
“…Based on the aforementioned clinical examination and in vitro studies ( 24 , 25 ), this study focused on the in vivo anticancer effect of the overexpression of RBM10 by treating mice with attenuated Salmonella carrying pcDNA3.1 (control group) or pcDNA3.1-RBM10. Salmonella is a facultative anaerobe that is able to grow in aerobic and anaerobic conditions and, therefore, may be used to deliver numerous types of therapeutic agents ( 30 ). This technique has been used to provide tumor-targeting bacteria that are able to deliver genes that encode pro-drug-converting enzymes, angiogenic inhibitors or cytokines ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the aforementioned clinical examination and in vitro studies ( 24 , 25 ), this study focused on the in vivo anticancer effect of the overexpression of RBM10 by treating mice with attenuated Salmonella carrying pcDNA3.1 (control group) or pcDNA3.1-RBM10. Salmonella is a facultative anaerobe that is able to grow in aerobic and anaerobic conditions and, therefore, may be used to deliver numerous types of therapeutic agents ( 30 ). This technique has been used to provide tumor-targeting bacteria that are able to deliver genes that encode pro-drug-converting enzymes, angiogenic inhibitors or cytokines ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of S. Typhimurium as a means of delivery has also been evaluated by its ability to easily penetrate and destroy tumour cells. Several promoters of S. Typhimurium that preferentially respond to the anaerobic environment of the tumour have been identified 86,87 and explored as delivery vehicles 88 for novel anticancer molecules such as Cp53 peptide and L-asparaginase 49 through genetic engineering of the organism, which has resulted in tumour regression. 6 The use of murine carcinoma cell lines showed that a recombinant strain of attenuated S. Typhimurium expressed a cytotoxin, encoded by the gene LIGHT, which had anti-tumour activity without any substantial toxicity.…”
Section: S Typhimurium As a Gene Delivery Vectormentioning
confidence: 99%
“…), and experimentally it has been proven that these promoters can be used to deliver novel anticancer molecules such as Cp53 peptide (Camacho et al . ), l ‐asparaginase ( l ‐ASnase) (Kim et al . ) through engineered Salmonella , which resulted in tumour regression (Nguyen et al .…”
Section: Salmonella: a Delivery Vehicle For Anticancer Moleculesmentioning
confidence: 99%